2011
DOI: 10.3989/scimar.03635.26c
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene to Holocene diversification and historical zoogeography of the Arabian killifish (<i>Aphanius dispar</i>) inferred from otolith morphology

Abstract: SUMMARY:Aphanius dispar (Rüppell, 1829) is a common marine-euryhaline teleost fish in the Near East that has undergone considerable intraspecific differentiation. Otolith morphology is used to analyse the diversity within A. dispar in the Gulf of Oman (Sea of Oman) and the Persian Gulf. A total of 134 individuals from lagoons and inland habitats of Oman, the United Arab Emirates and southern Iran are analysed. The results revealed that otolith traits that are under genetic control are strikingly different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…Because of these characteristics, otolith morphometry has been widely used to identify fish stocks (e.g. Among the most commonly used indexes are rectangularity, circularity, aspect ratio, OL/SuL (Burke et al, 2008;Tuset et al, 2008;Longmore et al, 2010;Cañas et al, 2012;Jaramilo et al, 2014;Avigliano et al, 2015c, among others), and recently, the RL/OL index has been widely used by various authors (Reichenbacher et al, 2007(Reichenbacher et al, , 2009Teimori et al, 2012a, b;Annabi et al, 2013;Reichenbacher & Reichard, 2014, otolith morphometry to identify triplefins among others). Nolf, 1985;Smale et al, 1995;Tuset et al, 2011;Tuset et al, 2013;Zhuang et al, 2014), and to describe ecomorphological patterns of species (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these characteristics, otolith morphometry has been widely used to identify fish stocks (e.g. Among the most commonly used indexes are rectangularity, circularity, aspect ratio, OL/SuL (Burke et al, 2008;Tuset et al, 2008;Longmore et al, 2010;Cañas et al, 2012;Jaramilo et al, 2014;Avigliano et al, 2015c, among others), and recently, the RL/OL index has been widely used by various authors (Reichenbacher et al, 2007(Reichenbacher et al, , 2009Teimori et al, 2012a, b;Annabi et al, 2013;Reichenbacher & Reichard, 2014, otolith morphometry to identify triplefins among others). Nolf, 1985;Smale et al, 1995;Tuset et al, 2011;Tuset et al, 2013;Zhuang et al, 2014), and to describe ecomorphological patterns of species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Enneapterygius paucifasciatus inhabits coral reefs in depths of 2 -4 m (Fricke, 2002), while E. gracilis occurs in shallow tidal pools (depth range 0-15 m) and seems to be associated with coralline rocks and seagrass (Fricke, 1994). For example, Reichenbacher et al (2009), Teimori et al (2012a and Reichenbacher & Reichard (2014) have observed a strong correlation between their RL index and genetic factors in species of killifishes. On the other hand, another cause could be related to a great genetic influence.…”
Section: Discussionmentioning
confidence: 99%
“…sulcus area, depth of the sulcus, sulcus area:otolith area ratio or shape) vary according to environmental, ontogenetic, phylogenetic and ecological factors (e.g. Nolf 1985, Lombarte 1992, Lombarte and Lleonart 1993, Paxton 2000, Gauldie and Crampton 2002, Volpedo and Echeverria 2003, Lombarte and Cruz 2007, Tuset et al 2010, Reichenbacher et al 2007, Teimori et al 2012. However, it is not known how otolith shape variability affects hearing ability Lu 2000, Popper et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study shed new light on previous work on the differences in otolith morphology between populations of Aphanius iberus (Reichenbacher and Sienknecht 2001) and A. dispar (Reichenbacher et al 2009a, 2009b, Teimori et al 2012a, 2012b. In these studies, otolith differences have been interpreted as indicating allopatric genetic divergence, but a test of this interpretation by molecular data analyses has not been conducted.…”
Section: Discussionmentioning
confidence: 67%